3‐D localization of non‐radioactive strontium in osteoarthritic bone: Role in the dynamic labeling of bone pathological changes. Issue 11 (3rd June 2015) - Panahifar, Arash; Cooper, David M.L.; Doschak, Michael R.
ABSTRACT: The study objective was to visualize regions of bone that undergo pathological mineralization and/or remodeling during pathogenesis of osteoarthritis, by employing non‐radioactive strontium as a dynamic tracer of bone turnover. Post traumatic osteoarthritis was surgically induced in skeletally mature rats, followed by in vivo micro‐CT imaging for 12 weeks to assess bone micro‐structural changes. Rats either received strontium ranelate daily for the entire course of study or only last 10 days before euthanization. Distribution of strontium in bone was assessed in two and three dimensions, using electron probe micro‐analysis (EPMA) and synchrotron dual energy K‐edge subtraction micro‐CT (SRμCT), respectively. Considerable early formation of osteophytes around the collateral ligament attachments and margins of articulating surfaces were observed, followed by subchondral sclerosis at the later stages. Accordingly, strontium was heavily incorporated by mineralizing osteophytes at 4, 8, and 12 weeks post‐surgery, whereas subchondral bone only incorporated strontium between weeks 8–12.This study showed low dose stable strontium can effectively serve as a dynamic tracer of bone turnover to study pathological bone micro‐structural changes, at resolution higher than nuclear medicine. Co‐administration of strontium during therapeutic drug intervention may show enormous utility in assessing the efficacy of those compounds upon adaptive bone physiology. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1655–1662, 2015.